Logoterapi efektif dalam meningkatkan harga diri, namun perlu berhati-hati: Studi meta analisis - Diadiningrum, Jihan Rahma; Yudiarso, Ananta (Mediapsi, 2022)
Individuals with positive self-esteem recognize their personal qualities. They feel comfortable, optimistic, and confident about themselves. Conversely, individuals with negative self-esteem tend to experience poor quality of life. This study examines the effectiveness of logotherapy in increasing self-esteem. We conducted a meta-analysis by collecting and reviewing 14 research articles on logotherapy and self-esteem. We analyzed the data from the selected articles based on the number of participants (N), the average value (M), and the standard deviation (SD). The meta-analysis showed that logotherapy is a recommended and effective intervention to increase self-esteem.   Keywords: logotherapy, meta-analysis, self-esteem